Degenerated annulus fibrosus of the intervertebral disc contains collagen type II. Issue 2 (April 1984) - Adam, M; Deyl, Z
Abstract : Collagen has been isolated and purified from the pronase digest of the outer annulus fibrosus of degenerated and unaffected intervertebral discs obtained at necropsy. The mixture of different collagen types has been purified and fractionated by 2 subsequent DEAE-cellulose chromatographic procedures according to established methods. Collagen chain polymers were then isolated by molecular sieving. Their reduction with 2-mercaptoethanol followed by agarose chromatography resulted in the separation of 3 major peaks corresponding to gamma, beta, and alpha chains. Cyanogen bromide (CNBr) peptides and aminoacid analyses revealed the identity of the isolated alpha-chain as alpha 1(III). Further support for this finding was obtained by immunofluorescence. It is suggested that the presence of collagen type III in the outer annulus fibrosus may be related to intervertebral disc prolapse.